THE PECULIARITIES OF FAMILY RELATIONSHIP IMPACT ON AGGRESSIVENESS OF ADOLESCENTS WITH ADDITIVE BEHAVIOR - Begheza, Ludmila; Trofimchuk, Victoria (PSYCHOLOGICAL JOURNAL, 2019)
The article describes the experimental study on the influence of family relationships on the aggressiveness of adolescents with addictive behavior. Based on performed theoretical study, the authors determine the aggressiveness of adolescents with addictive behavior as an integrated set of adolescents’ personal qualities, manifested in potential readiness for destructive actions under influence of harmful substances that can change mental states. The structure of such adolescents’ aggressiveness is identified, which contains cognitive, motivational, affective, and behavioral components. The article presents the methodical tools used at the empirical study to determine aggressiveness of adolescents with additive behavior and severity of certain relationships in their families. The article contains the results of theoretical studies performed by famous scientists who made attempts to define “aggressiveness”, “adolescents’ aggressiveness”, “additive behavior”. The empirical study aim was to determine family relationship influence on the aggressiveness of adolescents with additive behavior. According to the performed correlative analysis, there are correlations between aggressiveness of adolescents with additive behavior and severity of certain relationships in their families. The authors note that high aggressiveness is characteristic for adolescents brought up in families with hostile, aggressive moods; average aggressiveness is observed at adolescents living in families where parents give autonomy to their children; and low aggressiveness is observed at adolescents living in families where parents show positive interest to their children. The study results provide the basis for taking into account certain family features at the development of a program correcting adolescents’ aggressiveness.